IMPLEMENTASI PROGRAM SEMBAKO - Agnes Cellyana Nainggolan; Titi Stiawati; Juliannes Cadith (Jurnal Governansi, 2022)
Poor people in Indonesia finds difficulties in fulfilling their nutritional food needs. The Ministry of Social Affairs has implemented “sembako” program aimed at reducing the burden of the poor and vulnerable people in fulfilling some main food items. This research aims to describe the implementation of “sembako” program in Lebak Regency, Banten Province. This research regarding the implementation of “sembako” program is based on theory of policy implementation that emphasizes six dimensions, namely standards and objectives, resources, characteristics of implementing agencies, disposition of implementors, interorganizational commu-nication, and economic, social and political conditions. This research uses descriptive-qualitative method. Samples of this research are drawn on purposive and snowball sampling. The collection of data uses interview, observation, literature study, and documentation. The collected data are qualitatively described. Results of this research indicate that the implementation of “sembako” program in Lebak Regency, Banten Province, is not optimally conducted on dimensions of standards and objectives, resources, characteristics of implementing agencies, disposition of implementors, interorganizational communication, and economic, social and political conditions. Some causes are related to the lack of discipline of the local government apparatus, the lack of people’s awareness in completing assistance administration, the lack of inter-implementor coordination and communication, the occurrence of social jealousy because of poor people that do not obtain assistance yet, and the presence of political motives in selecting e-Warong and poor people that obtain assistance. Keywords: Policy Implementation, Public Policy, “Sembako” Program.